Analisisi Kekakuan Pelat Baja Galvanil Ketebalan 0,6 MM Akibat Pembentukan Dengan Metode Bead Rolled - M Fadillah, Febian; Erwanto, Erwanto (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
The cold forming process for thin plates is widely used and essential in the manufacturing industry, particularly in the automotive sector. One such cold-forming method is the bead roll process, commonly referred to as